Lifestyle breast cancer patients among Indonesian women: A nationwide survey - Solikhah Solikhah; Khairunnisaa Nuur Aliifah Setyawati; Monthida Sangruangake (International Journal of Public Health Science (IJPHS), 2021)
Recently, cancer is a major health problem in the world. Lifestyle changes and growing urbanization likely led to increasing breast cancer incidence in such in Indonesia. Therefore, this study aimed to explore lifestyle breast cancer patients among Indonesian women. The investigation was a cross-sectional study distributed among 3,392 females drawn from 13 out of 27 provinces in Indonesia. Multiple binary logistic regressions were conducted to investigate breast cancer risk among Indonesian. A significance level of 0.05 was employed in all analysis. Of the 3,392 respondents included in the analysis, more than half (52.71%; n=1,788) was aged 40–49 years old. The most common marital status of the participants was married (98.20%; n=3,331), followed by no smoking (94.69%; n=3,212) and active exercise (62.12%; n=2,107). Education level was significantly associated with breast cancer (AdjOR_Junior high school=0.21; 95%CI=0.06 to 0.70; p<0.01 and AdjOR_senior high school=0.60; 95%CI=0.15 to 2.26; p<0.05). Education level was significantly related to breast cancer. Lifestyle such as smoking and physical activity was suspected to affect breast cancer indirectly.